after life - Lidin, Konstantin (project baikal, 2025)
We don’t choose the times, We live and die in them. Alexander Kushner, 1978 An obligatory attribute of life is death. As the saying goes, “everyone will be there”, so it would be strange to ignore this important fact. Nevertheless, projects devoted to ‘architecture for those who have passed away’ are quite rare – at least, much rarer than projects ‘for the living’. However, both crematoria and cemeteries are still more necessary for the living than for the dead. The German word ‘Friedhof’ (cemetery) literally means ‘garden of peace’. Let the Past be remembered only with peace.